First Certificate Language Practice - Vince, Michael (Macmillan, 2003)
This text revises the main grammar points at the level of First Certificate as well as providing practice in key lexical areas. The book can be used as a self-study reference grammar and practice book or as supplementary material in classes preparing for examinations